Gastric Cancer and Angiogenesis: Is VEGF a Useful Biomarker to Assess Progression and Remission? - Macedo, F (2017)
Gastric cancer (GC) has high mortality owing to its aggressive nature. Tumor angiogenesis plays an essential role in the growth, invasion, and metastatic spread of GC. The aim of this work was to review the angiogenic biomarkers related to the behavior of GC, documented in the literature. A search of the PubMed database was conducted with the MeSH terms: "Stomach neoplasms/blood [MeSH] or stomach neoplasms/blood supply [MeSH] and angiogenic proteins/blood [Major]". A total of 30 articles were initially collected, and 4 were subsequently excluded. Among the 26 articles collected, 16 examined the role of vascular endothelial growth factor (VEGF), 4 studied endostatin, 3 investigated angiopoietin (Ang)-2, 2 studied the Ang-like protein 2 (ANGTPL2), and 1 each examined interleukin (IL)-12, IL-8, and hypoxia inducible factor. Regarding VEGF, 6 articles concluded that the protein was related to lymph node metastasis or distant metastases. Five articles concluded that VEGF levels were elevated in the presence of GC and decreased following tumor regression, suggesting that VEGF levels could be a predictor of recurrence. Four articles concluded that high VEGF levels were correlated with poor prognosis and lower survival rates. Ang-2 and ANGTPL2 were elevated in GC and associated with more aggressive disease. Endostatin was associated with intestinal GC. VEGF is the most extensively studied angiogenic factor. It is associated with the presence of neoplastic disease and lymph node metastasis. It appears to be a good biomarker for disease progression and remission, but not for diagnosis. The data regarding other biomarkers are inconclusive.